The Use of Lifting Straps Alters the Entire Load-Velocity Profile During the Deadlift Exercise - Jukic, Ivan; García-Ramos, Amador; Malecek, Jan; Omcirk, Dan; Tufano, James J (Journal of strength and conditioning research, 2020)
Jukic, I, García-Ramos, A, Malecek, J, Omcirk, D, and Tufano, JJ. The use of lifting straps alters the entire load-velocity profile during the deadlift exercise. J Strength Cond Res 34(12): 3331-3337, 2020-This study aimed to compare the one repetition maximum (1RM) and load-velocity (LV) profile between deadlifts performed with (DLw) and without (DLn) lifting straps. The full individual LV relationship of 20 men (age: 24.3 ± 2.4 years; body height: 180.6 ± 6.9 cm; body mass: 85.8 ± 8.0 kg) was randomly evaluated during 2 separate sessions for the DLw and DLn via an incremental loading test. One repetition maximum was greater (p < 0.001; g = 0.56, 95% confidence interval = [0.32, 0.79]) for DLw (177.0 ± 28.9 kg) compared with DLn (160.6 ± 26.0 kg). A highly linear relationship between mean velocity (MV) and %1RM was observed for both conditions (R > 0.95; SEE < 6.18 %1RM for pooled data and R > 0.98; SEE < 3.6 %1RM for individual data). However, MV associated with each %1RM was greater for DLn, and these differences were accentuated as the loading magnitude increased (g = 0.30-1.18). One repetition maximum was strongly associated between both conditions (r = 0.875 [0.71, 0.95]), whereas MV at 1RM (r = 0.21 [-0.25, 0.60]) was unrelated between conditions. The slope of the LV profiles (r = 0.845 [0.64, 0.94]) was correlated, but differed (g = 0.41 [0.16, 0.66]) between DLw and DLn, whereas the mean test velocity of all loads was unrelated (r = 0.270 [-0.20, 0.64]). An individual LV profile should be created for each athlete in the same condition that are going to be used in training to obtain a more precise estimation of the submaximal relative loads.
Keywords: svalová síla; Young Adult; Muscle Strength; Adult; Male; Body Height; vzpírání; dospělí; lidé; mužské pohlaví; cvičení; tělesná výška; odporový trénink; Weight Lifting; Humans; mladý dospělý; Exercise; Resistance Training